Rotating body for fixing, fixing device, and electrophotographic image forming apparatus

The fixing rotor with a silver-containing heat-generating layer partially filled with silicon dioxide and covered by a silicon dioxide layer and resin layer addresses resistance issues, maintaining consistent heat generation and fixation performance.

JP2025166411APending Publication Date: 2025-11-06CANON KK
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024070421
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2024-04-24
Publication Date
2025-11-06

AI Technical Summary

Technical Problem

The use of silver nanoink in forming heat-generating layers for fixing rotors in electrophotographic image forming apparatuses leads to increased resistance in non-paper-passing areas due to prolonged exposure to high temperatures, causing uneven heat generation and reduced fixation at paper edges, especially when printing small-sized papers.

Method used

A fixing rotor design featuring a resin substrate with a heat-generating layer containing silver, partially filled with silicon dioxide, and covered by a silicon dioxide layer and resin layer, which includes pores and openings, to prevent resistance increase and enhance durability.

Benefits of technology

The design provides a fixing rotor with enhanced durability and consistent heat generation even under prolonged high-temperature conditions, ensuring effective fixation across various paper sizes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025166411000001_ABST
    Figure 2025166411000001_ABST
Patent Text Reader

Abstract

To provide a rotating body for fixing excellent in durability even in such a printing environment in which a high temperature state continues for a long time.SOLUTION: A rotating body for fixing comprises: a resin base material; a heat generating layer extending on an outer peripheral surface of the resin base material; a silicon dioxide layer in an area where the heat generating layer is not present, on an outer peripheral surface of the heat generating layer and the outer peripheral surface of the resin base material; and a resin layer on an outer peripheral surface of the silicon dioxide layer. The heat generating layer contains silver. The heat generating layer has pores present with openings toward the resin layer and at least partially filled with silicon dioxide. Holes are present in the heat generating layer.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present disclosure relates to a fixing rotor used in a fixing device of an electrophotographic image forming apparatus such as an electrophotographic copying machine or printer, a fixing device, and an electrophotographic image forming apparatus. [Background technology]

[0002] A fixing device installed in an electrophotographic image forming apparatus such as an electrophotographic copier or printer generally heats a recording material carrying an unfixed toner image while transporting the recording material in a nip formed by a heated fixing rotor and a pressure roller in contact with the heated rotor, thereby fixing the toner image to the recording material. An electromagnetic induction heating type fixing device has been developed and put into practical use. The fixing device has a heating layer on the fixing rotor, and this heating layer can generate heat directly. The advantage of the electromagnetic induction heating type fixing device is that it has a short warm-up time. The heat generating layer is required to be conductive and durable against repeated distortion under heat. For example, Patent Document 1 discloses a fixing member having a heat generating layer with a predetermined pattern formed by copper plating. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent Publication No. 2021-051136 Summary of the Invention [Problem to be solved by the invention]

[0004] The inventors attempted to apply silver nanoink, which allows for fine control of line width and spacing, when forming the heat-generating layer, in the hope of minimizing uneven heat generation. Heat-generating layers formed with silver nanoink can be formed into thin layers, which is advantageous for flex resistance. Furthermore, the presence of submicron-sized pores provides a damping effect against compressive stress caused by pressure and heat application, suppressing buckling and other problems, and is expected to improve durability.

[0005] On the other hand, in the fixing rotor, there is a phenomenon in which the temperature of the components rises at the end where paper does not pass, i.e., the non-paper passing area. The fixing rotor is heated at all times to maintain the fixing temperature in order to reliably fix the toner in the paper passing area. In the paper passing area, the paper absorbs heat as it passes, so continuous heating is required. On the other hand, in the non-paper passing area, there is no exchange of heat due to the passage of paper, so the component temperature can rise above the set temperature. This phenomenon is particularly likely to occur in special usage environments, such as when printing small-size paper continuously.

[0006] The inventors discovered a new problem: when a fixing rotor using silver nanoink to produce a heat-generating layer is used, if the non-paper-passing area remains at a high temperature above the set value for a long period of time, the resistance of the heat-generating layer increases. When this increase in resistance occurs in the non-paper-passing area for small-sized paper, uneven heat generation due to electromagnetic induction occurs, and when fixing larger-sized paper, fixation at the edge of the paper decreases.

[0007] At least one aspect of the present disclosure is directed to a fixing rotor that is highly durable even in a printing environment where high temperatures persist for long periods of time. Also, at least one aspect of the present disclosure is directed to a fixing device and an electrophotographic image forming apparatus that include the fixing rotor. [Means for solving the problem]

[0008] The present disclosure provides: A fixing rotor, the fixing rotor comprising: A resin substrate; a heat generating layer extending on the outer peripheral surface of the resin substrate; a silicon dioxide layer on the outer peripheral surface of the heat generating layer and on the outer peripheral surface of the resin substrate in an area where the heat generating layer is not present; a resin layer on the outer peripheral surface of the silicon dioxide layer, the heat generating layer contains silver, the heat generating layer has holes at least partially filled with silicon dioxide and having openings on the resin layer side; The heat generating layer has pores. The present invention relates to a fixing rotating body characterized by the above-mentioned. [Effects of the Invention]

[0009] According to at least one aspect of the present disclosure, a fixing rotating body having excellent durability even in a printing environment where high temperatures continue for a long period of time is provided. According to at least one aspect of the present disclosure, there is also provided a fixing device including the fixing rotor. According to at least one aspect of the present disclosure, there is also provided an electrophotographic image forming apparatus including the fixing device. [Brief explanation of the drawings]

[0010] [Figure 1] 1 is a cross-sectional view of a heat generating layer formed from silver nanoink according to the present disclosure. [Figure 2] 1 is a schematic diagram illustrating an example of a configuration of an electrophotographic image forming apparatus. [Figure 3] FIG. 2 is a schematic diagram illustrating an example of a cross-sectional configuration of a fixing device. [Figure 4] FIG. 2 is a schematic diagram illustrating an example of a cross-sectional configuration of a fixing device. [Figure 5] FIG. 2 is a schematic diagram illustrating an example of a magnetic core and an excitation coil of a fixing device. [Figure 6] FIG. 2 is a diagram showing a magnetic field formed when a current is passed through an excitation coil. [Figure 7] FIG. 2 is a diagram illustrating an example of a cross-sectional configuration of a fixing rotating body. [Figure 8] FIG. 1 is a schematic diagram showing the film formation mechanism of silver nanoink. [Figure 9] 10A and 10B show a cross-sectional image and a binarized image of a heat generating layer of a fixing rotatable body according to the present disclosure. [Figure 10] 10 is a cross-sectional image of a heat generating layer of a fixing rotatable body according to the present disclosure. DETAILED DESCRIPTION OF THE INVENTION

[0011] In the present disclosure, expressions such as "XX or more and YY or less" or "XX to YY" representing a numerical range mean a numerical range including the upper and lower limits, which are the endpoints, unless otherwise specified. When a numerical range is described in stages, the upper and lower limits of each numerical range can be combined arbitrarily. Furthermore, in the present disclosure, expressions such as "at least one selected from the group consisting of XX, YY, and ZZ" mean any of XX, YY, ZZ, a combination of XX and YY, a combination of XX and ZZ, a combination of YY and ZZ, or a combination of XX, YY, and ZZ.

[0012] A fixing rotator having a heat generating layer according to the present disclosure, and a fixing device and an image forming apparatus including the fixing rotator will be described in detail below based on specific configurations. As mentioned above, when a fixing rotor using silver nanoink to manufacture the heat generating layer is used, if a high temperature state above the set temperature continues for a long period of time in the non-paper passing area, the resistance of the heat generating layer may increase. Figure 1 shows a cross-sectional view of a heat generating layer formed using silver nanoink. Heat generating layers formed using silver nanoink have the characteristics that the grain size of the silver crystals is smaller than when formed using bulk silver, and that the grain boundary area is very large due to the presence of voids 200a and voids 200b. Therefore, the area where silver reacts with oxygen becomes larger, and oxidation proceeds more easily than with bulk silver, which is thought to result in an increase in resistance.

[0013] The inventors have discovered that by forming a silicon dioxide layer on the outer peripheral surface of a silver-containing heat-generating layer, an increase in the resistance of the heat-generating layer can be suppressed even when the heat-generating layer is exposed to a high temperature for a long period of time, resulting in excellent durability of the fixing rotor even in a printing environment where the heat-generating layer is exposed to a high temperature for a long period of time. The reason why the formation of the silicon dioxide layer can suppress an increase in the resistance of the heat generating layer is that the dense silicon dioxide layer 200c covers the outer peripheral surface of the heat generating layer, and the silicon dioxide layer 200c acts as a barrier layer. Furthermore, the pores 200a that open to the outermost surface are filled with silicon dioxide. This is thought to be because the surface area of ​​the heat generating layer that comes into contact with oxygen is reduced, making it possible to suppress an increase in resistance even at high temperatures.

[0014] A fixing rotating member having a heat generating layer, and a fixing device and an electrophotographic image forming apparatus including the same will be described in detail below based on specific configurations. However, the dimensions, materials, shapes, and relative positions of the components described in this embodiment may be changed as appropriate depending on the configuration of the components to which the disclosure is applied and various conditions. In other words, the scope of this disclosure is not intended to be limited to the following embodiment. In addition, in the following description, components having the same function are denoted by the same numbers in the drawings, and their description may be omitted.

[0015] (Electrophotographic image forming apparatus) An electrophotographic image forming apparatus (hereinafter also simply referred to as "image forming apparatus") according to an embodiment of the present disclosure includes an image carrier that carries a toner image, a transfer device that transfers the toner image to a recording material, and a fixing device that fixes the transferred toner image to the recording material. The fixing device is a fixing device according to an embodiment of the present disclosure, which will be described later.

[0016] FIG. 2 is a cross-sectional view showing the overall configuration of a color laser beam printer (hereinafter, printer) 1, which is an example of an image forming apparatus equipped with a fixing device (image heating device) 15 according to an embodiment of the present disclosure. A cassette 2 is housed in the bottom of the printer 1 and can be pulled out. Cassette 2 holds a stack of sheets P as recording material. The sheets P in cassette 2 are separated one by one by a separation roller 3 and fed to a registration roller 4. Note that a variety of sheets of different sizes and materials can be used as the recording material sheet P, including paper such as plain paper and cardboard, surface-treated sheet materials such as plastic film, cloth, and coated paper, and sheet materials with special shapes such as envelopes and index paper.

[0017] The printer 1 includes an image forming unit 5 as an image forming means, which includes image forming units 5Y, 5M, 5C, and 5K corresponding to the colors yellow, magenta, cyan, and black, arranged side by side in a horizontal row. The image forming unit 5Y includes a photosensitive drum 6Y, which is an image carrier (electrophotographic photosensitive member), and a charging roller 7Y, which serves as charging means for uniformly charging the surface of the photosensitive drum 6Y. A scanner unit 8 is also provided below the image forming unit 5. The scanner unit 8 forms an electrostatic latent image on the photosensitive drum 6Y by irradiating the photosensitive drum 6Y with a laser beam that is on / off modulated in accordance with a digital image signal input from an external device such as a computer (not shown) and generated by an image processing means based on image information.

[0018] Furthermore, the image forming unit 5Y includes a developing roller 9Y as a developing means that attaches toner to the electrostatic latent image on the photosensitive drum 6Y to develop it into a toner image, and a primary transfer unit 11Y that transfers the toner image on the photosensitive drum 6Y to the intermediate transfer belt 10. Toner images formed in the other image forming units 5M, 5C, and 5K in the same process are superimposed and transferred onto the toner image on the intermediate transfer belt 10 transferred in the primary transfer unit 11Y. As a result, a full-color toner image is formed on the intermediate transfer belt 10. This full-color toner image is transferred onto the sheet P in the secondary transfer unit 12 as a transfer means. Primary transfer The transfer unit 11Y and the secondary transfer unit 12 are examples of a fixing device that fixes the transferred toner image onto the recording material.

[0019] Thereafter, the toner image transferred onto the sheet P (on the recording material) passes through a fixing device 15 and is fixed as a fixed image. The sheet P then passes through a discharge conveyance section 13 and is discharged and stacked on a stacking section 14. The image forming unit 5 is an example of an image forming means. Although the primary transfer unit 11Y and the secondary transfer unit 12 are exemplified as fixing devices, the fixing device may be, for example, a direct transfer type fixing device that directly transfers a toner image from an image carrier to a sheet P. The image forming device may also be configured as a monochrome type that uses toner of only one color.

[0020] (fixing device) The fixing device 15 according to an embodiment of the present disclosure is a fixing device (image heating device) including a fixing rotator according to an embodiment of the present disclosure, which will be described later, and an induction heating device that generates heat from the fixing rotator by induction heating (electromagnetic induction). Fig. 3 shows a cross-sectional configuration of the fixing device 15, and Fig. 4 is a perspective view of the fixing device 15. Note that the housing of the fixing device 15 and other components are omitted from Figs. 3 and 4. In the following description, with respect to the members that make up the fixing device 15, the longitudinal direction X1 is the direction perpendicular to the conveyance direction of the recording material and the thickness direction of the recording material, i.e., the direction of the rotation axis of the fixing rotator 20.

[0021] The fixing device 15 includes a fixing rotor 20, a film guide 25, a pressure roller 21, a pressure stay 22, a magnetic core 26, a thermistor 40, and a current sensor 30. The fixing device 15 heats a recording material on which an image has been formed, and fixes the image to the recording material. The fixing rotor 20 is the fixing rotor of this embodiment, and the pressure roller 21 is the opposing member of this embodiment. As shown in FIGS. 5 and 6, the fixing device 15 may also include an excitation coil 27 that functions as a magnetic field generating means of this embodiment. Details of the fixing rotor will be described later.

[0022] The fixing rotor 20 has a resin substrate 20a, a heat-generating layer 20b on the outer peripheral surface of the resin substrate 20a, and a resin layer present on the outer peripheral surface of the heat-generating layer 20b (the surface opposite the side facing the resin substrate 20a). A silicon dioxide layer (not shown) is present on the outer peripheral surface of the heat-generating layer and on the outer peripheral surface of the resin substrate in areas where the heat-generating layer is not formed, and the resin layer is formed on the outer peripheral surface of the silicon dioxide layer. The resin layer may be composed of multiple layers. The resin layers in FIGS. 3 and 4 are a protective layer 20c and a surface layer (release layer) 20d. The heat generating layer 20b can be formed as a heat generating pattern in which heat generating rings 201 (FIG. 4) are arranged in the longitudinal direction, each of which is formed in a ring shape electrically connected in the circumferential direction and electrically divided in the longitudinal direction X1 (the direction of the rotation axis of the fixing rotor 20). In other words, the heat generating layer 20b can be configured to have a plurality of segments that are arranged in the direction of the rotation axis of the fixing rotor and are electrically isolated from one another, and each of the plurality of segments is electrically continuous over the entire circumferential direction of the fixing rotor. It is preferable that each of the heat generating rings 201, which is a component of the heat generating pattern, is formed with a uniform width in the longitudinal direction X1.

[0023] The pressure roller 21, which serves as an opposing body (pressure member) facing the fixing rotor 20, includes a core 21a and an elastic layer 21b that is molded concentrically around the core to form a roller-like coating, with a release layer 21c provided on its surface. The elastic layer 21b is preferably made of a highly heat-resistant material such as silicone rubber, fluororubber, or fluorosilicone rubber. Both longitudinal ends of the core 21a are rotatably held between metal plates on the chassis (not shown) of the device via conductive bearings. As shown in FIG. 4, pressure springs 24a and 24b are respectively compressed between both longitudinal ends of the pressure stay 22 and spring bearing members 23a and 23b on the device chassis side, thereby applying a downward force to the pressure stay 22.

[0024] In the fixing device 15 of this embodiment, it is preferable to apply a total pressing force of approximately 100 N to 300 N (approximately 10 kgf to approximately 30 kgf). As a result, the lower surface of the film guide 25, which is made of a heat-resistant resin such as polyphenylene sulfide (PPS), and the upper surface of the pressure roller 21 are pressed against each other across the fixing rotor 20, which is a cylindrical rotor, to form a nip N of a predetermined width. The film guide 25, together with the pressure roller 21, functions as a nip forming member that forms the nip that sandwiches and conveys the recording material carrying a toner image via the fixing rotor 20.

[0025] 3 by a driving means (not shown), and applies a counterclockwise rotational force to the fixing rotor 20 due to friction with the outer surface of the fixing rotor 20. As a result, the fixing rotor 20 rotates while sliding on the film guide 25.

[0026] 5 is a schematic diagram of the magnetic core 26 and the exciting coil 27 in FIG. 3, and the fixing rotor 20 is indicated by a dashed line to explain the positional relationship with the fixing rotor 20. An induction heating device in an induction heating type fixing device that heats the fixing rotor 20 by electromagnetic induction may include the magnetic core 26 and the exciting coil 27. The exciting coil 27 is disposed inside the fixing rotor 20. The exciting coil 27 has a spiral-shaped portion whose spiral axis is approximately parallel to the direction along the rotation axis of the fixing rotor 20, and forms an alternating magnetic field that causes the heat-generating layer 20b to generate heat through electromagnetic induction. "Approximately parallel" does not mean that the two axes are completely parallel, but rather that a slight misalignment is allowed to allow the heat-generating layer to generate heat through electromagnetic induction.

[0027] The magnetic core 26 is disposed in the spiral portion, extends in the direction of the rotation axis of the fixing rotor 20, and does not form a loop outside the fixing rotor 20. The magnetic core 26 guides the magnetic field lines of the alternating magnetic field.

[0028] 5, the magnetic core 26 is inserted into the hollow portion of the fixing rotor 20, which is a cylindrical rotor. The exciting coil 27 is wound spirally around the outer periphery of the magnetic core 26 and extends in the longitudinal direction of the fixing rotor 20. The magnetic core 26 has a cylindrical shape and is fixed by a fixing means (not shown) so as to be located approximately in the center of the fixing rotor 20 in a cross section viewed in the longitudinal direction (see FIG. 3).

[0029] The magnetic core 26 provided inside the excitation coil 27 has the role of guiding the magnetic field lines (magnetic flux) of the alternating magnetic field generated by the excitation coil 27 inward from the heat generating layer 20b of the fixing rotor 20, and forming a path (magnetic path) for the magnetic field lines. The material of the magnetic core 26 is preferably a material with low hysteresis loss and high relative permeability, such as at least one high-permeability soft magnetic material selected from the group consisting of sintered ferrite, ferrite resin, etc.

[0030] The cross-sectional shape of the magnetic core 26 need not be circular as long as it can be accommodated in the hollow portion of the fixing rotor 20, but a shape that allows for as large a cross-sectional area as possible is preferable. The diameter of the magnetic core 26 is preferably 5 to 20 mm, more preferably 8 to 12 mm. In the fixing device used in the examples of the present disclosure, the diameter of the magnetic core 26 was 10 mm, and the longitudinal length was 280 mm. The excitation coil 27 is formed by spirally winding a copper wire (single conductor) with a diameter of 1 to 2 mm coated with heat-resistant polyamideimide around the magnetic core 26, preferably 5 to 40 turns, more preferably 10 to 30 turns. In the fixing device used in the examples of the present disclosure, the excitation coil 27 was formed by spirally winding 20 turns. The excitation coil 27 is wound around the magnetic core 26 in a direction intersecting the rotation axis direction of the fixing rotor 20. Therefore, when a high-frequency alternating current is applied to this excitation coil 27, an alternating magnetic field is generated in a direction parallel to the rotation axis direction, and each of the heat generating layers 20b of the fixing rotor 20 An induced current (circulating current) flows through the heat generating ring 201, generating heat, according to a principle that will be described later.

[0031] As shown in FIGS. 3 and 4, the thermistor 40 serving as temperature detection means for detecting the temperature of the fixing rotor 20 is composed of a spring plate 40a and a thermistor element 40b. The spring plate 40a is a support member having spring elasticity that extends toward the inner surface of the fixing rotor 20. The thermistor element 40b serving as a temperature detection element is installed at the tip of the spring plate 40a. The surface of the thermistor element 40b is covered with an insulator such as polyimide tape to ensure electrical insulation. The thickness of the insulator is preferably 10 to 100 μm, more preferably 25 to 75 μm. In the fixing device used in the examples of the present disclosure, a polyimide tape with a thickness of 50 μm was used.

[0032] The thermistor 40 is fixed to the film guide 25 and installed at approximately the center of the fixing rotor 20 in the longitudinal direction. The thermistor element 40b is pressed against the inner surface of the fixing rotor 20 by the spring elasticity of the spring plate 40a, and is maintained in contact with the inner surface. The thermistor 40 may also be arranged on the outer periphery of the fixing rotor 20. The current sensor 30, which constitutes a continuity monitoring device that monitors the circumferential conduction of the heat-generating layer 20b, is located at the same position as the thermistor 40 in the longitudinal direction of the fixing device 15. In other words, the current sensor 30 monitors the conduction state of the heat-generating ring 201 that is in contact with the thermistor element 40b, among the multiple heat-generating rings 201 that constitute the heat-generating pattern of the fixing rotor 20. The current sensor 30 is composed of an outer magnetic core 30a, an inner magnetic core 30b, and a detection coil 30c. The current sensor 30 detect ... detects the conduction state of the heat-generating ring 201 that is in contact with the thermistor element 40b, among the multiple heat-generating rings 201 that constitute the heat-generating pattern of the fixing rotor 20. The current sensor 30 detects the conduction state of the heat-generating ring 201 that is in contact with the thermistor element 40b, among the multiple heat-generating rings 201 that constitute the heat-generating pattern of the fixing rotor 20. The current sensor 30 detects the conduction state of the heat-generating ring 201 that is in contact with the thermistor element Therefore, the secondary current generated in the detector coil 30c also changes. By measuring the change in the secondary current in the detector coil 30c, it is possible to detect whether or not a continuity defect has occurred.

[0033] (Heating principle) The heating principle of the fixing rotor 20 in the induction heating type fixing device 15 will now be described. Fig. 6 is a conceptual diagram showing the moment when current increases in the direction of the arrow I0 in the excitation coil 27. The excitation coil 27 is inserted into the fixing rotor 20 and functions as a magnetic field generating means that generates an induced current I in the circumferential direction of the fixing rotor 20 by passing an alternating current through it.

[0034] Furthermore, the magnetic core 26 functions as a component that induces magnetic field lines B (dotted lines in FIG. 6) generated by the excitation coil 27 and forms a magnetic path. While typical induction heating methods involve magnetic field lines penetrating the heat-generating layer to generate eddy currents, in this embodiment, the magnetic field lines B loop around the outside of the fixing rotor. That is, the heat-generating layer 20b is primarily heated by the induced currents induced by the magnetic field lines that emerge from one longitudinal end of the magnetic core 26, pass outside the heat-generating layer 20b, and return to the other longitudinal end of the magnetic core 26. This allows for efficient heat generation even when the heat-generating layer is as thin as 5 μm or less.

[0035] When an alternating magnetic field is formed by the excitation coil 27, an induced current I according to Faraday's law flows in each heat-generating ring 201 of the heat-generating layer 20b of the fixing rotor 20. Faraday's law states that "when the magnetic field in a circuit is changed, an induced electromotive force that tries to cause a current to flow in the circuit is generated, and the induced electromotive force is proportional to the time change in the magnetic flux that penetrates the circuit perpendicularly." Consider the induced current I that flows through heat-generating ring 201c located in the center of magnetic core 26 in the longitudinal direction shown in Fig. 6 when a high-frequency alternating current is passed through excitation coil 27. When a high-frequency alternating current is passed, an alternating magnetic field is formed inside magnetic core 26. The induced electromotive force acting on heat-generating ring 201c at this time is proportional to the change over time in the magnetic flux that perpendicularly penetrates the inside of heat-generating ring 201c, according to the following formula:

[0036]

number

[0037] This induced electromotive force V causes an induced current I, which is a circular current circulating through the heat-generating ring 201c, to flow, and the heat-generating ring 201c generates heat due to Joule heat generated by the induced current I. However, if the heat-generating ring 201c is broken, the induced current I does not flow, and the heat-generating ring 201c does not generate heat.

[0038] A fixing rotating body according to an embodiment of the present disclosure (hereinafter also simply referred to as a fixing rotating body) includes: A resin substrate; a heat generating layer extending on the outer peripheral surface of the resin substrate; a silicon dioxide layer on the outer peripheral surface of the heat generating layer and on the outer peripheral surface of the resin substrate in an area where the heat generating layer is not present; a resin layer on the outer peripheral surface of the silicon dioxide layer, the heat generating layer contains silver, the heat generating layer has holes at least partially filled with silicon dioxide and having openings on the resin layer side; The heat generating layer has pores. The fixing rotating body is characterized by the above.

[0039] (1) Outline of the fixing rotor The fixing rotor will be described in detail with reference to the drawings. The fixing rotor may be a rotatable member, such as an endless belt. FIG. 7 is a circumferential cross-sectional view of an example of a fixing rotor. The fixing rotor includes a cylindrical resin substrate 20a containing at least a resin, a heat-generating layer 20b on the outer peripheral surface of the resin substrate 20a, and a resin layer c present on the outer peripheral surface of the heat-generating layer 20b (the surface opposite the surface facing the resin substrate 20a). A silicon dioxide layer (not shown) is present on the outer peripheral surface of the heat-generating layer and on the outer peripheral surface of the resin substrate in areas where the heat-generating layer is not formed, and the resin layer is formed on the outer peripheral surface of the silicon dioxide layer. The resin layer is a layer containing resin, and a specific example is the protective layer 20c described below. The resin layer may be composed of multiple layers, and may include an elastic layer 20e and a surface layer (release layer) 20d, as necessary, on the outer peripheral side of the protective layer 20c. An adhesive layer 20f may also be present between the elastic layer 20e and the surface layer 20d. FIG. 7 shows an example of a fixing rotor having, as resin layers, a protective layer 20c, an elastic layer 20e, an adhesive layer 20f, and a surface layer (releasing layer) 20d in this order from the inner periphery of the fixing rotor.

[0040] (2) Resin substrate The material of the resin substrate 20a is not particularly limited as long as it contains at least a resin. That is, the resin substrate 20a contains a resin. When the belt is used in an electromagnetic induction type fixing device, it is preferable that the resin substrate 20a is a layer that changes little in physical properties and can maintain high strength when the heat generating layer 20b, which is a conductive layer, generates heat. For this reason, it is preferable that the resin substrate 20a contains a heat-resistant resin as a main component, and is preferably made of a heat-resistant resin. A thermoplastic resin is a resin that does not melt or decompose at temperatures below, for example, 200°C (preferably below 250°C).

[0041] The resin contained in the resin substrate 20a (preferably the resin constituting the resin substrate) is preferably at least one selected from the group consisting of polyimide (PI), polyamideimide (PAI), modified polyimide, and modified polyamideimide. More preferably, it is at least one selected from the group consisting of polyimide and polyamideimide. Among these, polyimide is particularly preferred. In the present disclosure, the term "main component" refers to the component that is contained in the largest amount by mass among the components constituting the object (here, the resin substrate).

[0042] The modified polyimide and modified polyamideimide may be modified by siloxane, carbonate, fluorine, urethane, triazine, or phenol.

[0043] In the fixing rotating member, the material of the resin base material 20a is analyzed in the following procedure. A sample of the resin substrate, 10 mm square and 10 mm thick, is cut out from the fixing rotor. If there is an elastic layer or surface layer, remove it with a razor or solvent before cutting out the sample. The material of the obtained sample is confirmed by performing attenuated total reflection (ATR) measurement using an infrared spectrometer (FT-IR) (product name: Frontier FT IR, manufactured by PerkinElmer). The material of the resin layer, which will be described later, is also analyzed in the same manner as above.

[0044] The resin base material 20a may contain a filler to improve heat insulation and strength. The shape of the resin substrate can be appropriately selected depending on the shape of the fixing rotary member, and can be various shapes such as an endless belt shape, a hollow cylinder shape, a film shape, and the like. When the fixing rotatable body is a fixing belt, the thickness of the resin substrate 20a is, for example, preferably 10 to 100 μm, more preferably 20 to 60 μm. By setting the thickness of the resin substrate 20a within the above range, it is possible to achieve both high levels of strength and flexibility.

[0045] In addition, on the inner surface of the resin substrate (the surface opposite to the side facing the heat generating layer 20b), for example, a layer for preventing wear of the inner surface of the fixing rotor when the inner surface of the fixing rotor comes into contact with other members, or a layer for improving sliding properties with other members may be provided.

[0046] Since other members such as sliding members are disposed on the inner surface of the resin base material 20a and the sliding load is large, it is preferable that the resin base material be a solid layer in order to ensure durability as a resin base material. The solid layer is a layer that does not substantially contain voids within the layer. "Substantially does not contain voids" means that voids are not intentionally provided, but the presence of voids that are inevitably mixed in due to scratches, cracks, chips, etc. is allowed. The presence or absence of voids can be observed by observing the cross section of the substrate. The cross section of the substrate can be observed in the same manner as the cross section observation of the protective layer described below. The substrate 20a can have a solid layer by using a cylindrical substrate that is molded without substantial voids. For example, in the case of thermosetting resins such as polyimide and polyamideimide, when the solvent in the coating film evaporates during molding, the sudden temperature rise can cause bumping, forming voids. Therefore, when volatilizing the solvent in the coating film, it is preferable to select a treatment temperature and treatment time that will prevent bumping. The outer peripheral surface of the resin base material 20a may be subjected to a roughening treatment such as blasting, or a modification treatment such as ultraviolet light, plasma, or chemical etching in order to improve adhesion and wettability with the heat generating layer 20b.

[0047] (3) Heat generating layer The heat-generating layer 20b is a layer that generates heat when current is applied. In the principle of heat generation by induction heating using an excitation coil, when an alternating current is supplied to an excitation coil arranged near the fixing rotor, a magnetic field is induced, and this magnetic field generates a current in the heat-generating layer 20b of the fixing rotor, which generates heat due to Joule heat. The heat-generating layer extends in the circumferential direction of the outer circumferential surface of the resin substrate.

[0048] The heat generating layer 20b contains silver. Silver has a low volume resistivity and is resistant to oxidation. The silver content of the entire heat generating layer 20b is preferably 90.0 mass% or more, more preferably 99.0 mass% or more, and particularly preferably 99.9 mass% or more. The upper limit is, for example, 99.999 mass% or less, or 99.99 mass% or less. The silver content of the entire heat generating layer 20b is preferably 90.0 to 99.999 mass%, more preferably 99.9 to 99.99 mass%.

[0049] The volume resistivity of the heat generating layer 20b is preferably 1.0×10 -8 ~8.0×10 -8 Ω m, 2.0×10 -8 ~7.0×10 -8 Ω m, 2.0×10 -8 ~6.0×10 -8 Examples include the Ω·m range. The volume resistivity of the heat generating layer 20b can be reduced by increasing the purity or content of silver contained in the heat generating layer 20b. The volume resistivity can be measured by peeling off the resin layer with a cutter and then using a four-terminal resistance measurement method.

[0050] The silver contained in the heat generating layer 20b is preferably silver crystal, and the number-average crystal grain size of the silver crystals is preferably 500 nm or less. The number-average crystal grain size of the silver crystals is preferably 50 to 500 nm, more preferably 100 to 200 nm, and even more preferably 150 to 180 nm. When the number-average crystal grain size is within the above range, even when the fixing rotor 20 is pressurized and deformed in the nip portion N and subjected to repeated stress, numerous stable crystal interfaces are formed in the heat generating layer 20b, suppressing the occurrence of cracks at the crystal interfaces and providing excellent durability. By forming the heat generating layer 20b using silver nanoink or the like, which will be described later, it is possible to include silver crystals in the heat generating layer 20b. The number average crystal grain size of the silver crystals can be adjusted by the grain size of the silver nanoparticles blended into the silver nanoink or the like.

[0051] The heat generating layer has pores. Specifically, at least one pore exists in a cross section perpendicular to the circumferential direction of the heat generating layer. The presence of pores in the heat generating layer reduces the difference between the compressive modulus of the heat generating layer 20b in the compression direction and the compressive modulus of the resin constituting the resin substrate and resin layer due to a damper effect. If the difference in compressive modulus between the resin constituting the resin substrate and resin layer and the heat generating layer is small, excessive stress can be prevented from being applied to the interface between the conductive layer and the resin constituting the resin substrate and resin layer when the edge of the paper, the so-called paper edge, is subjected to localized compressive deformation. It is preferable to adjust the amount and size of the pores.

[0052] Therefore, from the viewpoint of electrical conductivity and durability, the compressive elastic modulus in a region of 10 to 20% in the thickness direction of the heat generating layer, measured by contacting an indenter with the surface of the heat generating layer opposite the surface facing the silicon dioxide layer, is preferably 5 to 50 GPa, more preferably 8 to 30 GPa, and particularly preferably 9 to 15 GPa. The method for measuring the compressive elastic modulus will be described in detail later in the Examples. The compressive elastic modulus can be decreased by increasing the porosity of the heat generating layer, and can be increased by decreasing the porosity of the heat generating layer. It should be noted that pores completely filled with silicon dioxide or resin material do not exert a damping effect and do not contribute to a decrease in the compressive modulus. Therefore, in order to achieve both the effect of suppressing the increase in resistance due to the filling of silicon dioxide and the improvement in mechanical durability due to the damping effect, it is preferable to limit the amount of pores filled with silicon dioxide to an appropriate range. As long as the compressive modulus is within the above-mentioned range, there is no particular restriction on the proportion of pores filled with silicon dioxide or resin, but the amount of pores that are filled may be increased. It is preferable that the number of pores filled with silicon dioxide or resin is half or less of the number of pores that are not filled with silicon dioxide or resin. Whether or not the pores are filled with silicon dioxide or resin can be determined by EDS images described below.

[0053] Methods for providing pores in the heat generating layer 20b include, for example, forming a pattern on the heat generating layer 20b by a photolithography process and then forming holes by chemical etching, or by using a laser or a focused ion beam. In this disclosure, we will particularly describe the formation of pores using a silver nanoparticle material.

[0054] The heat-generating layer is preferably a fired silver nanoink coating. When a coating containing silver nanoparticles with a particle size of approximately 10 to 50 nm is formed, the heat-generating layer becomes porous with the particles stacked together, as shown in Figure 8A. Due to the unstable surface energy of silver nanoparticles, the particles fuse together even when fired at a low temperature of approximately 100°C, and a film with nano-sized pores can be formed, as shown in Figure 8B. The size and number of pores can be expressed as the porosity.

[0055] Specifically, the porosity of the cross section of the heat generating layer, measured by observing a cross section of the heat generating layer sampled from the fixing rotor and cut in the thickness direction, is preferably 15 to 50 area %, more preferably 15 to 45 area %, and even more preferably 17 to 40 area %. By keeping the porosity within the above range, it is easy to control the compressive elastic modulus of the heat generating layer within a preferred range, resulting in excellent conductivity and durability. The porosity can be increased by increasing the temperature during firing of the heat generating layer, and can be decreased by decreasing the temperature during firing of the heat generating layer.

[0056] The number average crystal grain size and porosity of silver in the heat generating layer are determined as follows. First, a sample for evaluation is prepared. A sample measuring 5 mm in length, 5 mm in width, and the entire thickness of the fixing rotor is taken from the center of the fixing rotor in the direction of its rotation axis. The cross section of the obtained sample perpendicular to the circumferential direction of the fixing rotor is polished using an ion beam. The polishing position is adjusted so that the cross section perpendicular to the circumferential direction of the heat generating layer is exposed by the ion beam polishing. An ion milling device (product name: IM4000, manufactured by Hitachi High-Technologies Corporation) is used for cross-section polishing using an ion beam. Cross-section polishing using an ion beam can prevent filler from falling off from the sample and abrasive contamination, and can also form a cross-section with fewer polishing marks.

[0057] Next, an osmium coater (trade name: Tennant 20) was used to form a 3 nm-thick thin film on the processed cross section to impart conductivity. The cross section of the heating layer was then observed using a scanning electron microscope (SEM) (trade name: JSM-F100, manufactured by JEOL Ltd.), and cross-sectional images and EDS (Energy Dispersive X-ray Spectroscopy) images were acquired. The observation area was a 12.8 μm × 9.6 μm area, with the center of the heating layer's thickness aligned with the vertical center of the SEM image. The observation conditions were a 10,000x backscattered electron image mode, and the backscattered electron image acquisition conditions were an accelerating voltage of 5.0 kV and a working distance of 10 mm. EDS images were also acquired under these conditions.

[0058] Next, the obtained image is binarized using commercially available image software so that the silver-containing metal crystal particle portion is white and the other portion is black. Specifically, the backscattered electron image is read using ImageProPlus, an image analysis software manufactured by Media Cybernetics, and the brightness distribution of this image is determined. Next, by setting the brightness range of the determined brightness distribution, binarization is performed to distinguish between the silver-containing metal crystal particle and the other portion. The binarization method used is Otsu's method.

[0059] Then, lines separating the crystal grains, obtained from the contrast difference between the crystal grains in the cross-sectional image (Figure 9A) due to differences in brightness or crystal orientation, are added to the binarized image to obtain a binarized image in which each crystal grain is separated (Figure 9B). The black areas in Figure 9B represent pores in the heat generating layer or materials of layers other than the heat generating layer, such as polyimide or polyamideimide resin substrates. The open pores on the outer peripheral surface of the heat generating layer are filled with the silicon dioxide of the present disclosure (Figure 1, 200a). Whether silicon dioxide is filled can be confirmed by checking the EDS image for the distribution of Si and O elements in the pores on the outer peripheral surface of the heat generating layer. Locations in the EDS image where Si and O are present at 5% or more are considered to be locations where a silicon dioxide layer is formed or filled. In the present disclosure, it is important to prevent air from flowing through the resin layer into the pores that open to the resin layer (the outer peripheral surface of the heat generating layer). The silicon dioxide filling of the pores means that at least a portion of the pore is filled, preferably at least the opening of the pore is filled with silicon dioxide, and more preferably the entire inner surface of the pore is filled with silicon dioxide. In addition, whether or not the material of layers other than the heat generating layer (such as polyimide or polyamide) is filled can be determined by whether or not 5% or more of carbon is present in the EDS image of the pores, just like with silicon dioxide.

[0060] We will now explain how to calculate the number average crystal grain size from the binarized images of the cross section of the heating layer obtained in this way. Because digital image processing technology is applied to these images, it is assumed that all images are in a general digital image format with pixels arranged in a grid pattern. Furthermore, the binarized images are grayscale images containing only brightness information, and the images obtained by subsequently performing image processing on these images are all grayscale images in the same format unless otherwise noted.

[0061] First, the circle-equivalent diameter of each crystal particle is calculated. Note that the circle-equivalent diameter of each crystal particle refers to the diameter of a circle having the same area as the crystal particle. Specifically, the number of pixels constituting each crystal particle is calculated, and the actual area of ​​the crystal particle is calculated by multiplying this number of pixels by the area of ​​one pixel. In the SEM images used in this disclosure, the length of one side of one pixel corresponds to 0.01 μm, so the number of pixels that each crystal grain constitutes is 0.01 × 0.01 μm 2 Furthermore, the diameter of a circle having this area is calculated to calculate the equivalent circle diameter. The total of the equivalent circle diameters of the crystal grains thus obtained is divided by the total number of crystal grains to calculate the number average crystal grain size. Here, a total of six measurement samples are collected as follows: That is, as described above, one sample is collected from the central portion of the fixing rotor in the direction of the rotation axis. Furthermore, when the length of the fixing rotor in the direction of the rotation axis is L, one sample is collected from a portion 0.1 L away from the central portion in the direction of the rotation axis. From each of these collection points, samples are similarly collected at portions 120° and 240° away in the circumferential direction of the fixing rotor, for a total of six samples.

[0062] The above procedure was repeated for six samples taken from the fixing rotor, and the number-average crystal grain size of each sample was calculated. The arithmetic mean of these six number-average crystal grain sizes was then calculated to determine the number-average crystal grain size of the silver crystals in the heating layer.

[0063] A method for calculating the porosity from the binarized image of the cross section of the heating layer thus obtained will be described. From the binarized image obtained by the above procedure, an image measuring 2.0 μm x 2.0 μm is cut out. Four images are cut out from one SEM image. The position from which the image is cut out is such that the center in the thickness direction of the heat generating layer is the center in the vertical direction of the cut out image. In addition, the four images are cut out so that the spacing between them is the same in the direction perpendicular to the thickness direction of the heat generating layer. This operation is performed on six SEM images to obtain cross-sectional images at 24 locations.

[0064] Each particle of the silver-containing metal crystal is shown as a white area, and the area of ​​each of these crystal particles in the image is calculated. Specifically, the number of pixels that make up each crystal particle is calculated, and the total number of pixels is calculated. This total number of pixels is multiplied by the area of ​​one pixel, 0.01 x 0.01 μm. 2By multiplying this by , the area occupied by the crystal grains can be calculated. As mentioned above, the blackened areas are voids and materials other than the heat generating layer. Therefore, the area of ​​the blackened areas occupied by materials of layers other than the heat generating layer is calculated. Specifically, the number of pixels constituting each material other than the heat generating layer is calculated, and the total number of pixels is calculated. This total number of pixels is multiplied by the area of ​​one pixel, 0.01 x 0.01 μm. 2 By multiplying this by , the area occupied by materials other than the heat generating layer can be calculated.

[0065] The porosity indicates the proportion of space that is not occupied by crystal particles or materials other than the heat generating layer. Therefore, using the area occupied by the crystal particles and the area occupied by materials other than the heat generating layer calculated above, the porosity can be calculated as follows: Porosity (%)=(2.0×2.0(μm 2 )-area occupied by crystal grains (μm 2 ) - Area occupied by materials other than the heating layer (μm 2 ))÷(2.0×2.0(μm 2 ))×100 This can be expressed as: The above porosity calculation is performed for 24 locations within a range of 2.0 μm×2.0 μm in size on the cross-sectional image of the heat generating layer, and the average porosity obtained by arithmetically averaging is taken as the porosity of the heat generating layer.

[0066] The thickness of the heat generating layer 20b is preferably 10.0 μm or less, and more preferably 5.0 μm or less. This is because the fixing rotor needs to have adequate flexibility and a small heat capacity. Another advantage is improved bending resistance. As shown in FIG. 3, the fixing rotor 20 is rotated while being pressed by the film guide 25 and the pressure roller 21. With each rotation, the fixing rotor 20 is pressurized and deformed at the nip N, and is subjected to stress. It is preferable to design the heat-generating layer 20b of the fixing rotor 20 so that it will not break due to fatigue even if it continues to be repeatedly bent over the lifespan of the fixing device. Reducing the thickness of the heat-generating layer 20b significantly improves the resistance of the heat-generating layer 20b to fatigue failure. This is because, when the heat-generating layer 20b is pressed and deformed to fit the curved surface of the film guide 25, the thinner the heat-generating layer 20b, the smaller the internal stress acting on the heat-generating layer 20b.

[0067] For the above reasons, from the viewpoint of further improving resistance to a decrease in heat capacity and fatigue fracture, the thickness of the heat generating layer 20b is preferably 10.0 μm or less, and more preferably 5.0 μm or less. There is no particular lower limit, but examples include 1.0 μm or more and 2.0 μm or more. Examples of the thickness of the heat generating layer 20b include 1.0 to 10.0 μm, 1.0 to 5.0 μm, 2.0 to 5.0 μm, and 2.0 to 4.0 μm.

[0068] The heat generating layer 20b extends in the circumferential direction of the outer peripheral surface of the resin base material 20a. The heat generating layer 20b may be configured in a predetermined pattern as long as it is capable of generating heat when energized. In particular, from the viewpoint of safety, a configuration in which a plurality of ring-shaped heat generating layers 20b are formed around the circumferential direction of the fixing rotor and electrically separated in the axial direction, as shown in FIG. 4, is preferred. This configuration can suppress localized temperature increases if cracks occur in the heat generating layer 20b. It is preferable that the width of the ring shape in the axial direction of the rotor is approximately constant. When such a pattern configuration is adopted, the surface area of ​​the heat generating layer 20b increases, but in this disclosure, the presence of a silicon dioxide layer, which will be described later, makes it possible to suppress deterioration due to oxidation.

[0069] The width of the ring of the heat generating layer 20b is preferably 100 μm or more from the viewpoint of manufacturability and heat generation, more preferably 200 μm or more, and even more preferably 300 μm or more. From the viewpoint of uneven heat generation and safety, it is preferably 1000 μm or less, more preferably 900 μm or less, and even more preferably 700 μm or less. The width of the ring is, for example, 100 to 1000 μm, 200 to 900 μm, or 300 to 700 μm.

[0070] The spacing between the rings of the heat generating layer 20b is preferably 50 μm or more, more preferably 100 μm or more, from the viewpoints of manufacturability and heat generation. From the viewpoint of uneven heat generation, the spacing is preferably 400 μm or less, more preferably 300 μm or less. The spacing between the rings may be, for example, 50 to 400 μm or 100 to 300 μm.

[0071] As mentioned above, a silicon dioxide layer is present on the outer peripheral surface of the heat generating layer. The method for forming the silicon dioxide layer is not particularly limited, but includes physical vapor deposition (PVD), chemical vapor deposition (CVD), solution coating, dipping, spraying, etc. The silicon dioxide layer of the present disclosure is characterized by being placed on the outer peripheral surface of the heat generating layer and filling the pores of the silver-containing heat generating layer that open to the resin layer side. As described above, the heat generating layer formed using silver nanoink is porous, has smaller crystal grain size than bulk silver, and has pores 200b, resulting in a very large grain boundary area. This increases the area that reacts with oxygen, making oxidation more likely to progress than with bulk silver, and increasing resistance. Therefore, it is preferable to cover the outer peripheral surface of the heat generating layer with a silicon dioxide layer without any gaps.

[0072] Such a silicon dioxide layer can be formed, for example, by impregnation with a polysilazane solution. Application methods include dipping, flow coating, and contact application using a sponge. In this disclosure, the application method using a sponge will be described. To impregnate the heat-generating layer with polysilazane solution, for example, a urethane sponge is impregnated with the polysilazane solution, and the solution is applied by tracing the outer surface of the laminate on which the heat-generating layer has been formed, followed by heating to form a film. Figure 10 shows the silicon dioxide layer permeating the heat-generating layer. Holes 200b, which have no openings, remain open. On the other hand, 200a in Figure 10 appears to be a closed hole at first glance, but it is actually filled with silicon dioxide. This indicates that the polysilazane solution has permeated through an opening somewhere in the depth direction or a narrow opening, filling the hole with silicon dioxide. Even if the holes are not completely filled, as long as the openings are blocked by the silicon dioxide layer, oxygen penetration is prevented, and the effects of the present disclosure are realized.

[0073] The thickness of the film formed varies depending on the viscosity of the solution, but application and heating are repeated until the required film thickness is reached. Considering that the silicon dioxide layer is subjected to repeated stress as a fixing rotor, the thickness is 2.00 μm or less, more preferably 1.50 μm or less, and particularly preferably 1.00 μm or less. There is no particular lower limit, but examples include 0.10 μm or more and 0.50 μm or more. The thickness of the silicon dioxide layer is, for example, 0.10 to 2.00 μm, 0.50 to 1.50 μm, or 0.50 to 1.00 μm. Here, the film thickness of the silicon dioxide layer is defined by measuring the thickness of the silicon dioxide layer formed on the outer peripheral surface of the resin substrate in the region where the heat-generating layer is not formed. On the other hand, silicon dioxide does not penetrate into the pores that are not open to the outer peripheral surface, and the pores are maintained. Therefore, the aforementioned advantage of resisting stress in the compressive direction is not lost in any way.

[0074] A suitable polysilazane solution is one in which perhydropolysilazane (PHPS) is dissolved in an organic solvent. Examples include the Silica Shield series manufactured by Excia Co., Ltd. and the Durazan series manufactured by Merck Performance Materials, LLC. These solutions can form a highly cross-linked silicon dioxide layer through hydrolysis at relatively low temperatures, for example, from 100°C to 250°C. The process for preparing the laminate constituting the fixing rotating body according to the present disclosure includes, for example, a process for obtaining a resin substrate, and a process for applying silver nanoink to the outer peripheral surface of the obtained resin substrate and baking it to obtain a heat-generating layer.

[0075] The process for obtaining the resin substrate is not particularly limited. For example, the resin substrate may be formed into an endless belt-shaped or roller-shaped resin substrate. For example, the resin material of the resin substrate may be applied to the surface of a cylindrical mold or the like, and heated as necessary to obtain the resin substrate.

[0076] Next, a silver nanoink is applied to the outer peripheral surface of the obtained resin substrate, and the resin substrate is baked (sintered) to form a heat-generating layer. The baking temperature is not particularly limited, but is preferably 150 to 450°C, and more preferably 250 to 350°C. In other words, the heat-generating layer is preferably a baked body (sintered body) of silver nanoparticles. The baking time is also not particularly limited, and may be, for example, 10 to 120 minutes.

[0077] (4) Resin layer In the present disclosure, the portion including the protective layer 20c, the elastic layer 20e, the adhesive layer 20f, and the surface layer 20d may be referred to as a resin layer. The resin layer may be only one protective layer or only one surface layer.

[0078] (5) Protective layer The fixing rotor may have a protective layer on the outer peripheral surface of the silicon dioxide layer. The protective layer 20c protects the heat generating layer 20b and has the functions of ensuring insulation and improving the strength of the heat generating layer 20b. The material constituting the protective layer 20c is not particularly limited. The material of the protective layer 20c is preferably a layer containing at least a resin. When the belt is used in an electromagnetic induction type fixing device, similar to the resin substrate 20a, the protective layer 20c is preferably a layer that exhibits little change in physical properties and maintains high strength when the heat-generating layer 20b generates heat.

[0079] For this reason, the protective layer 20c preferably contains a heat-resistant resin, more preferably contains a heat-resistant resin as a main component, and is preferably made of a heat-resistant resin. The heat-resistant resin is a resin that does not melt or decompose at temperatures below 200°C (preferably below 250°C), for example. The resin constituting the protective layer 20c preferably contains at least one selected from the group consisting of polyimide (PI), polyamideimide (PAI), modified polyimide, and modified polyamideimide. More preferably, it contains at least one selected from the group consisting of polyimide and polyamideimide. The modification is the same as that described for the resin substrate 20a. Among these, polyimide is particularly preferable. The term "main component" refers to the component that is contained in the largest amount among the components that make up the object (here, the protective layer). There are no particular limitations on the method for forming the resin substrate 20a or the protective layer 20c. For example, an imide-based material can be formed into a film by applying a liquid called a varnish using a known method and baking it.

[0080] The protective layer 20c may contain a thermally conductive filler from the viewpoint of heat transferability. By containing the thermally conductive filler, the thermal transferability of the protective layer 20c is improved, and the improved thermal transferability allows the heat generated in the heat-generating layer 20b to be efficiently transferred to the outer circumferential surface of the fixing rotor.

[0081] The thickness of the protective layer 20c is preferably 10 to 100 μm, more preferably 20 to 60 μm. From the perspective of the bending resistance of the heat-generating layer 20b, the thickness of the protective layer 20c is preferably adjusted so that the heat-generating layer 20b is located on the neutral axis. The neutral axis refers to the position within the cross section where tensile and compressive forces are balanced when a bending moment is applied to a component. If the neutral axis is located within the conductive layer, the tensile and compressive stresses applied to the conductive layer are minimized, reducing the occurrence of phenomena that lead to increased resistance, such as cracks and permanent deformation, and improving durability. Even if the neutral axis is not located on the conductive layer, positioning the neutral axis on the protective layer side can shift the stress applied to the conductive layer to the compressive side, thereby improving durability compared to when tensile stress is applied. In the fixing rotor, the neutral axis can be calculated from the thickness and elastic modulus of resin substrate 20a and the thickness and elastic modulus of protective layer 20c because the elastic layer and surface layer, which have low elastic modulus, have almost no effect. Specifically, by adjusting the thickness of each layer so that the product of the thickness y1 and elastic modulus E1 of the protective layer matches the product of the thickness y2 and elastic modulus E2 of the resin substrate, heat-generating layer 20b can be positioned on the neutral axis.

[0082] (6) Elastic layer The fixing rotor may have an elastic layer 20e on the outer periphery of the protective layer 20c. The elastic layer 20e is a layer that imparts flexibility to the fixing rotor to ensure a fixing nip in the fixing device. When the fixing rotor is used as a heating member that comes into contact with toner on paper, the elastic layer 20e also functions as a layer that imparts flexibility to the surface of the heating member so that it can follow the unevenness of the paper.

[0083] The elastic layer 20e includes, for example, rubber as a matrix and particles dispersed in the rubber. More specifically, the elastic layer 20e preferably includes rubber and a thermally conductive filler, and is preferably made of a cured product obtained by curing a composition including at least rubber raw materials (base polymer, crosslinking agent, etc.) and the thermally conductive filler. From the viewpoint of realizing the above-mentioned functions of the elastic layer 20e, the elastic layer 20e is preferably made of a cured silicone rubber containing thermally conductive particles, and more preferably made of a cured addition-curing type silicone rubber composition. The thickness of the elastic layer is, for example, 100 to 1000 μm, or 200 to 500 μm.

[0084] The silicone rubber composition may contain, for example, thermally conductive particles, a base polymer, a crosslinking agent, a catalyst, and, if necessary, additives. Because the silicone rubber composition is often liquid, the thermally conductive filler is easily dispersed therein, and the elasticity of the elastic layer 20e to be produced can be easily adjusted by adjusting the degree of crosslinking depending on the type and amount of the thermally conductive filler. The matrix functions to impart elasticity to the elastic layer 20e. From the viewpoint of imparting the above-described functions of the elastic layer 20e, the matrix preferably contains silicone rubber. Silicone rubber is preferable because it has high heat resistance, allowing it to maintain flexibility even in environments where the temperature in the non-paper passing area reaches as high as approximately 240°C. As the silicone rubber, for example, a cured product of an addition-curing liquid silicone rubber composition, which will be described later, can be used. The elastic layer 20e can be formed by applying and heating the liquid silicone rubber composition by a known method.

[0085] The liquid silicone rubber composition typically contains the following components (a) to (d): Component (a): organopolysiloxane having an unsaturated aliphatic group; Component (b): an organopolysiloxane having silicon-bonded active hydrogen; Component (c): catalyst; Component (d): Thermally conductive filler Each component will be described below.

[0086] Component (a) The organopolysiloxane having an unsaturated aliphatic group is an organopolysiloxane having an unsaturated aliphatic group such as a vinyl group, and examples thereof include those represented by the following formulas (1) and (2). [ka] In formula (1), m 1 represents an integer of 0 or more (preferably 500 to 1100), and n 1 represents an integer of 3 or more (preferably 10 to 40). 1 each independently represents a monovalent unsubstituted or substituted hydrocarbon group that does not contain an unsaturated aliphatic group, provided that R 1 At least one of R represents a methyl group. 2 each independently represents an unsaturated aliphatic group.

[0087] [ka] In formula (2), n 2 represents a positive integer (preferably 500 to 1100), and R 3 each independently represents a monovalent unsubstituted or substituted hydrocarbon group that does not contain an unsaturated aliphatic group, provided that R 3 At least one of R represents a methyl group. 4 each independently represents an unsaturated aliphatic group.

[0088] In formulas (1) and (2), R 1 and R 3 Examples of the monovalent unsubstituted or substituted hydrocarbon group containing no unsaturated aliphatic group that can be represented by include the following groups: Unsubstituted hydrocarbon groups Alkyl groups (e.g., methyl, ethyl, propyl, butyl, pentyl, hexyl). Aryl groups (for example, phenyl groups). Substituted hydrocarbon groups Substituted alkyl groups (for example, chloromethyl, 3-chloropropyl, 3,3,3-trifluoropropyl, 3-cyanopropyl, 3-methoxypropyl).

[0089] The organopolysiloxanes represented by formulas (1) and (2) have at least one methyl group directly bonded to the silicon atom that forms the chain structure. 1 and R 3 Preferably, 50% or more of each group is a methyl group, and all of the R 1 and R 3 is more preferably a methyl group. In addition, in formulas (1) and (2), R 2 and R 4 Examples of unsaturated aliphatic groups that can be represented by include the following groups. That is, examples of unsaturated aliphatic groups include vinyl groups, allyl groups, 3-butenyl groups, 4-pentenyl groups, and 5-hexenyl groups. Among these groups, R 2and R 4 is preferably a vinyl group.

[0090] From the viewpoint of moldability, the viscosity of component (a) is 1000mm 2 / s or more 50000mm 2 / s or less is preferable, and 3000 mm 2 / s or more 20000mm 2 / s or less is more preferable. 2 / s or more, the hardness required for the elastic layer 20e It is now easier to adjust the angle to 50,000mm. 2 When the kinematic viscosity is 1 / s or less, the viscosity of the composition does not become too high, making it easy to apply. The viscosity (kinematic viscosity) can be measured using a capillary viscometer, a rotational viscometer, or the like in accordance with JIS Z 8803:2011. The blending amount of component (a) is preferably 55% by volume or more from the viewpoint of durability and 65% by volume or less from the viewpoint of heat conductivity, based on the liquid silicone rubber composition used to form the elastic layer 20e.

[0091] Ingredient (b) The organopolysiloxane having silicon-bonded active hydrogen atoms functions as a crosslinker that reacts with the unsaturated aliphatic groups of component (a) under the action of a catalyst to form a cured silicone rubber. Any organopolysiloxane having a Si-H bond can be used as component (b). In particular, from the viewpoint of reactivity with the unsaturated aliphatic group of component (a), those having an average of three or more hydrogen atoms bonded to silicon atoms per molecule are preferably used. Specific examples of component (b) include the linear organopolysiloxane shown in formula (3) below and the cyclic organopolysiloxane shown in formula (4) below.

[0092] [ka] In formula (3), m 2 represents an integer of 0 or more (preferably 10 to 30), and n3 represents an integer of 3 or more (preferably 5 to 20), and R 5 each independently represents a monovalent unsubstituted or substituted hydrocarbon group that does not contain an unsaturated aliphatic group.

[0093] [ka] In formula (4), m 3 represents an integer of 0 or more (preferably 10 to 30), and n 4 represents an integer of 3 or more (preferably 5 to 20), and R 6 each independently represents a monovalent unsubstituted or substituted hydrocarbon group that does not contain an unsaturated aliphatic group.

[0094] R in formulas (3) and (4) 5 and R 6 Examples of the monovalent unsubstituted or substituted hydrocarbon group not containing an unsaturated aliphatic group that can be represented by R 1 Among these, R 5 and R 6 Preferably, 50% or more of each group is a methyl group, and all of the R 5 and R 6 is more preferably a methyl group. The content of component (b) is preferably 0.1 to 5.0 parts by mass, more preferably 0.2 to 3.0 parts by mass, per 100 parts by mass of component (a).

[0095] Ingredient (c) Examples of catalysts used in forming silicone rubber include hydrosilylation catalysts for accelerating the curing reaction. Known substances such as platinum compounds and rhodium compounds can be used as the hydrosilylation catalyst. The amount of catalyst used can be appropriately determined and is not particularly limited.

[0096] Ingredient (d) Examples of the thermally conductive filler include metals, metal compounds, and carbon fibers. Highly thermally conductive fillers are more preferred, and specific examples thereof include the following materials: Silicon metal (Si), silicon carbide (SiC), silicon nitride (Si3N4), boron nitride (BN), aluminum nitride (AlN), alumina (Al2O3), zinc oxide (ZnO), magnesium oxide (MgO), silica (SiO2), copper (Cu), aluminum (Al), silver (Ag), iron (Fe), nickel (Ni), vapor grown carbon fiber, PAN-based (polyacrylonitrile) carbon fiber, pitch-based carbon fiber. These fillers can be used alone or in combination of two or more.

[0097] From the viewpoint of handling and dispersibility, the average particle size of the filler is preferably from 1 μm to 50 μm, more preferably from 3 μm to 30 μm, where the average particle size refers to the volume average particle size. The filler may be spherical, pulverized, needle-like, plate-like, or whisker-like in shape. From the viewpoint of dispersibility, spherical fillers are particularly preferred. Furthermore, at least one of a reinforcing filler, a heat-resistant filler, and a coloring filler may be added. The content of the filler in the elastic layer is preferably 20 to 80% by volume, more preferably 30 to 60%, based on the elastic layer, from the viewpoint of hardness and thermal conductivity of the elastic layer.

[0098] (7) Adhesive layer The fixing rotor may have an adhesive layer 20f on the outer peripheral surface of the elastic layer 20e for adhering the surface layer 20d (described later). The adhesive layer 20f is a layer for adhering the elastic layer 20e and the surface layer 20d together. The adhesive used for the adhesive layer 20f can be appropriately selected from known adhesives and is not particularly limited. However, from the viewpoint of ease of handling, it is preferable to use an addition-curing silicone rubber containing a self-adhesive component. This adhesive may contain, for example, a self-adhesive component, an organopolysiloxane having a plurality of unsaturated aliphatic groups, typically vinyl groups, in the molecular chain, a hydrogenorganopolysiloxane, and a platinum compound as a crosslinking catalyst. The adhesive applied to the surface of the elastic layer 20e is cured by an addition reaction to form an adhesive layer 20f that bonds the surface layer 20d to the elastic layer 20e.

[0099] Examples of the self-adhesive component include the following: A silane having at least one, preferably two or more functional groups selected from the group consisting of an alkenyl group such as a vinyl group, a (meth)acryloxy group, a hydrosilyl group (SiH group), an epoxy group, an alkoxysilyl group, a carbonyl group, and a phenyl group. · Organosilicon compounds such as cyclic or linear siloxanes having 2 to 30 silicon atoms, preferably 4 to 20 silicon atoms. A non-silicon-based (i.e., silicon-free) organic compound that may contain oxygen atoms in the molecule, provided that it contains one to four, preferably one to two, aromatic rings such as monovalent to tetravalent, preferably divalent to tetravalent, phenylene structures per molecule, and at least one, preferably two to four, functional groups that can participate in a hydrosilylation addition reaction (e.g., alkenyl group, (meth)acryloxy group) per molecule.

[0100] The above self-adhesive components may be used alone or in combination of two or more. Furthermore, in order to adjust viscosity and ensure heat resistance, a filler component may be added to the adhesive within the scope of the present disclosure. Examples of such filler components include the following: Silica, alumina, iron oxide, cerium oxide, cerium hydroxide, carbon black, etc.

[0101] The blending amounts of each component contained in the adhesive are not particularly limited and can be set as appropriate. Such addition-curing silicone rubber adhesives are commercially available and easily available. The thickness of the adhesive layer 20f is preferably 20 μm or less. By setting the thickness of the adhesive layer 20f to 20 μm or less, when the fixing belt according to this embodiment is used as a heating belt in a thermal fixing device, the thermal resistance can be easily set low and heat from the inner surface side can be efficiently transferred to a recording medium. The thickness of the adhesive layer 20f can be, for example, 1 to 20 μm, or 2 to 10 μm.

[0102] (8) Surface layer The fixing rotor may have a surface layer 20d. The surface layer 20d preferably contains a fluororesin to function as a release layer that prevents toner from adhering to the outermost peripheral surface of the fixing rotor. The surface layer 20d may be formed, for example, by molding one of the resins listed below into a tube shape, or by coating the surface layer 20d with a resin dispersion. Tetrafluoroethylene-perfluoro(alkyl vinyl ether) copolymer (PFA), polytetrafluoroethylene (PTFE), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), etc. Among the resin materials exemplified above, PFA is particularly suitable from the viewpoint of moldability and toner releasability.

[0103] The thickness of the surface layer 20d is preferably 10 μm to 50 μm, inclusive, which makes it easier to maintain an appropriate surface hardness of the fixing rotor. [Example]

[0104] The present disclosure will be described in more detail below using examples, but the present disclosure is not limited to these examples.

[0105] [Example 1] A cylindrical stainless steel mold with an outer diameter of 30 mm was subjected to a release treatment, and a commercially available polyimide precursor solution (U Varnish S, manufactured by Ube Industries, Ltd.) was applied by immersion to form a coating film. The coating film was then dried at 140°C for 30 minutes to volatilize the solvent, followed by baking at 200°C for 30 minutes and 400°C for 30 minutes to imidize the film, forming a resin substrate with a polyimide film 40 μm thick and 300 mm long.

[0106] Next, a ring-shaped pattern with a width of 600 μm and intervals of 200 μm was formed on this resin substrate using a dispenser with a silver nanoparticle-containing ink (DNS351S, manufactured by Daicel Corporation). After that, the substrate was baked at 300° C. for 30 minutes to form a heat generating layer 20b with a thickness of 2.5 μm, and a laminate was obtained.

[0107] Next, a silicon dioxide layer was formed on the outer peripheral surface of the heat generating layer of the laminate and on the outer peripheral surface of the resin substrate in areas where the heat generating layer was not formed, by the following method. Polysilazane solution (Mark, Durazan 2400-15) was applied to a urethane sponge. The laminate was impregnated, coated on its surface in a tracing manner, and then baked for 1 hour at 200° C. The resulting silicon dioxide layer had a thickness of 0.85 μm.

[0108] Next, a PAI solution (Viromax HR-16NN, manufactured by Toyobo Co., Ltd.) was applied to the entire surface of the silicon dioxide layer by ring coating, and baked at 250° C. for 60 minutes to form a protective layer 20c with a thickness of 50 μm. Next, a primer (product name: DY39-051A / B, manufactured by Dow-Toray Industries, Inc.) was applied approximately uniformly to the outer surface of the protective layer 20c so that the dry weight was 40 mg, and after the solvent was dried, the layer was baked for 30 minutes in an electric furnace set to 160°C.

[0109] A silicone rubber composition layer having a thickness of 250 μm was formed on this primer by ring coating, and was subjected to primary crosslinking at 160° C. for 1 minute, followed by secondary crosslinking at 200° C. for 30 minutes to form the elastic layer 20e.

[0110] The silicone rubber compositions used were as follows: As component (a), an organopolysiloxane having an alkenyl group, a vinylated polydimethylsiloxane having at least two vinyl groups per molecule (trade name: DMS-V41, manufactured by Gelest, number average molecular weight 68,000 (polystyrene equivalent), molar equivalent of vinyl group 0.04 mmol / g) was prepared. Furthermore, as component (b), an organopolysiloxane having Si-H groups, a methylhydrogenpolysiloxane (trade name: HMS-301, manufactured by Gelest, number average molecular weight 1300 (polystyrene equivalent), molar equivalent of Si-H groups 3.60 mmol / g) having at least two Si-H groups per molecule was prepared. 0.5 parts by mass of component (b) was added to 100 parts by mass of component (a) and thoroughly mixed to obtain an addition-curing silicone rubber stock solution.

[0111] Furthermore, a catalytic amount of an addition curing reaction catalyst (platinum catalyst: platinum carbonylcyclovinylmethylsiloxane complex) and an inhibitor were added as component (c) and mixed thoroughly. High-purity spherical alumina (product name: Alnabeads CB-A10S, manufactured by Showa Titanium Co., Ltd.) was mixed as component (d), a thermally conductive filler, into this addition-cure silicone rubber stock solution at a volume ratio of 45% based on the elastic layer, and then kneaded to obtain an addition-cure silicone rubber composition with a JIS K 6253A durometer hardness of 10° after curing.

[0112] Next, an addition-curing silicone rubber adhesive (product name: SE1819CV A / B, manufactured by Dow-Toray Industries, Inc.) for forming adhesive layer 20f was applied uniformly to a thickness of approximately 20 μm onto the resulting elastic layer 20e, and a fluororesin tube (product name: NSE, manufactured by Gunze Co., Ltd.) with an inner diameter of 29 mm and a thickness of 30 μm for forming surface layer 20d was laminated on top of this while expanding its diameter.

[0113] The belt surface was then uniformly rubbed from above the fluororesin tube to remove excess adhesive from between the elastic layer 20e and the fluororesin tube, thinning the adhesive layer 20f to approximately 5 μm. The adhesive was then cured by heating at 200°C for 30 minutes, and the fluororesin tube was fixed onto the adhesive layer 20f and removed from the stainless steel mold. Finally, both ends were cut to a length of 240 mm, yielding a fixing rotor. The number-average crystal grain size of silver in the heat-generating layer of the resulting fixing rotor was 160 nm, and the porosity was 29%. Furthermore, the pores present on the outer peripheral surface of the heat-generating layer and opening toward the resin layer were entirely filled with silicon dioxide.

[0114] [Example 2] The silicon dioxide layer was formed in the same manner as in Example 1, except that the method was changed to one in which a polysilazane solution (Silica Shield SSL-SD500, manufactured by Excia Co., Ltd.) was impregnated into a urethane sponge, which was then applied to the surface of the laminate in a tracing manner, followed by baking at 250°C for one hour, which was repeated three times. Thus, a fixing rotor was obtained. The thickness of the silicon dioxide layer obtained was 0.90 μm. The number-average crystal grain size of the silver in the heat-generating layer of the obtained fixing rotor was 180 nm, and the porosity was 30%. Furthermore, the pores on the outer peripheral surface of the heat-generating layer that opened to the resin layer side were completely filled with silicon dioxide.

[0115] [Example 3] A fixing rotor was produced in the same manner as in Example 1, except that the coating and baking steps were repeated twice in the method of forming the silicon dioxide layer. The thickness of the obtained silicon dioxide layer was 1.5 μm. The number-average crystal grain size of silver in the heat-generating layer was 190 nm, and the porosity was 29%. Furthermore, the pores present on the outer peripheral surface side of the heat-generating layer and opening on the resin layer side were completely filled with silicon dioxide.

[0116] [Example 4] The fixing rotor was prepared in the same manner as in Example 1, except that the heating layer was baked at 150°C for 30 minutes. The resulting silicon dioxide layer had a thickness of 0.85 μm. The number-average crystal grain size of silver in the heat generating layer was 135 nm, and the porosity was 10%. Furthermore, the pores present on the outer peripheral surface of the heat generating layer and opening to the resin layer side were completely filled with silicon dioxide.

[0117] [Example 5] A fixing rotor was produced in the same manner as in Example 1, except that the coating conditions were changed so that the film thickness of the heat generating layer was 5.5 μm. The thickness of the obtained silicon dioxide layer was 0.80 μm. The number average crystal grain size of silver in the heat generating layer was 200 nm, and the porosity was 39%. Furthermore, the pores present on the outer peripheral surface side of the heat generating layer and opening on the resin layer side were completely filled with silicon dioxide.

[0118] [Example 6] This was produced in the same manner as in Example 2, except that after forming the heat generating layer, a silicon dioxide layer was formed by spray coating. The thickness of the resulting silicon dioxide layer was 0.80 μm. The number average crystal grain size of silver in the heat generating layer was 200 nm, and the porosity was 41%. Furthermore, the pores present on the outer peripheral surface of the heat generating layer and opening on the resin layer side were partially filled with silicon dioxide.

[0119] [Comparative Example 1] Except for not forming the silicon dioxide layer after forming the heat generating layer, the heat generating layer was produced in the same manner as in Example 1. The number average crystal grain size of silver in the heat generating layer was 180 nm, and the porosity was 39%.

[0120] Comparative Example 2 Except for forming the heat generating layer 20b by silver plating, a fixing rotor was produced in the same manner as in Example 1. The heat generating layer 20b was formed by silver plating in the following manner. A cylindrical polyimide film was prepared and a ring-shaped masking material was placed on its surface. A silver plating bath, consisting of potassium silver cyanide, was then used. The pH of the plating bath was maintained at 8-9, and the temperature at 50-70°C. After removal from the plating bath, the film underwent a cleaning process, and the masking material was removed, yielding a base layer with a 2.5 μm-thick heat-generating layer.

[0121] (Evaluation: Resistance fluctuation rate) (High temperature test) The fixing rotors manufactured in each example and comparative example were cut in half, one half was used for evaluating the initial resistance, and the other half was used for evaluation after heating (high-temperature test). The high-temperature test was performed by storing the fixing rotors at atmospheric pressure and 240°C for 200 hours. This storage temperature was set at a specific operating environment (when small-size paper was printed continuously) when the fixing rotor was actually incorporated into a fixing device and used. The temperature was set based on the expected overheating temperature in the non-paper passing portion.

[0122] (Resistance measurement method) The resistance variation rate was evaluated using contact resistance measurement. When measuring the resistance, the resin layer was peeled off with a cutter and the measurement was performed using the four-terminal resistance measurement method. The details of the resistance measurement are described below. Resistance measurements were made using a HIOKI 3541 resistance meter and two FormFactor FPC-GS-500 probes. The mode was set to low power mode, and the probes were pressed against the heating layer so that the distance between each sense probe was 20 mm, and the resistance value was measured. The volume resistivity value was converted from the width and film thickness of the heating layer. The same measurements were made before and after heating, and the value before heating was taken as the initial value, and the variation in volume resistivity from the initial value was evaluated. The results are shown in Table 1.

[0123] (Evaluation: Compressive modulus) The compressive elastic modulus of the heat generating layer was measured by the following method. First, the surface layer and elastic layer were peeled off from the fixing rotor, and the laminate of the resin substrate, heat-generating layer, and resin layer was taken out. Next, a polyimide coating remover (eSolv 21KZE-100, Kaneko Chemical Co., Ltd.) was used. The resin substrate was coated with the above-mentioned adhesive and heated at 40°C for 10 minutes. After cooling to room temperature, the sample was washed with pure water and dried to remove the resin substrate, exposing the heat-generating layer on the side opposite the silicon dioxide layer. The compressive modulus of the exposed heat-generating layer was measured using a Berkovich indenter with a microindentation hardness tester (product name: Nanoindenter G200, manufactured by Agilent Technologies).

[0124] The measurement area was determined by pressing the heat generating layer to a depth of 1 μm in the thickness direction from the surface opposite the surface facing the silicon dioxide layer, and calculating the average compressive elastic modulus at each depth position measured in a region of 10 to 20% of that depth, i.e., a region from 0.1 μm to 0.2 μm from the surface, to calculate the average elastic modulus in this region. The results are shown in Table 1.

[0125] (Evaluation: actual machine durability test) A paper feed durability test was conducted under the following conditions for the fixing rotors of Examples 1 to 6 and Comparative Examples 1 and 2. Each fixing rotor was incorporated into a fixing device, which was then mounted on a laser printer. A paper feed durability test was conducted in which 500,000 sheets of B5-sized recording material were printed without printing any images in an environment of 15°C temperature and 10% humidity. Every 10,000 sheets, A4-sized recording material was printed to check for deformation of the paper edge and fixability at the edge. The laser printer was based on a Satera LBP961Ci (product name) manufactured by Canon Marketing Japan Inc., and was capable of rotating the pressure roller and fixing rotor at a higher speed than normal (linear velocity of 400 mm / s). A modified apparatus was used. The recording material used for paper feeding was NPI wood-free paper (B5 size, 120 μm thick, manufactured by Nippon Paper Industries Co., Ltd.). The recording material used for printing was A4 size NPI wood-free thick paper (A4 size, 148 μm thick, manufactured by Canon Marketing Japan Inc.), and printing was performed to check for image defects. The results are shown in Table 1. The results of the actual machine durability test were ranked according to the following criteria. Rank A: No image defects even after 500,000 sheets have been printed. Rank B: After 500,000 sheets have been printed, there is a slight image defect. Rank C: Minor image defects were observed before 500,000 sheets were fed. Rank D: Image defects occurred after passing less than 200,000 sheets.

[0126] [Table 1] In Table 1, "Ag" represents silver, "PAI" represents polyamideimide, and "PI" represents polyimide.

[0127] In Example 3, the silicon dioxide layer was thicker than in Example 1. As a result, minor fixing defects were observed in areas corresponding to non-paper-passing areas of B5-size paper after 500,000 sheets were passed. This is thought to be because the thick silicon dioxide layer caused slight cracks during repeated bending and durability testing, reducing its oxygen inhibition function, resulting in an increase in resistance in the high-temperature environment of the non-paper-passing areas. In Example 4, a fixing rotor with a lower porosity of the heat-generating layer compared to Example 1 was obtained. As a result, minor streak-like image defects occurred when printing A4-size paper. This is thought to be due to slight deformation occurring at a position corresponding to the edge of B5-size paper. In Example 5, minor image defects occurred at the edge when printing A4-size paper. In a static heating evaluation, the resistance fluctuation rate was 3.5%, but because the heat-generating layer was thickened to 5.5 μm, minor cracks occurred on the surface of the heat-generating layer due to bending stress during paper-passing durability testing, resulting in an increase in resistance.

[0128] In Comparative Example 1, each evaluation was carried out without providing a silicon dioxide layer. Therefore, a resistance increase at high temperatures was confirmed in a preliminary heating evaluation. During a paper feed durability test on an actual machine, after feeding 150,000 sheets of B5 size paper, image defects occurred at the edges when feeding A4 size paper. This is thought to be because a resistance increase occurred in the area corresponding to the non-paper feed area of ​​B5 size paper. In Example 6, a silicon dioxide layer was provided. The installation was done by spray coating. Because of the spray coating, some of the opened holes were filled with silicon dioxide, but the silicon dioxide layer was not able to be formed completely inside the opened holes, so the resistance fluctuation rate at high temperatures was a little large at 12%, and even during the paper feed durability test at 200,000 sheets, minor image defects occurred in the position corresponding to the non-paper feed area of ​​B5 size paper.

[0129] In Comparative Example 2, the heat generating layer was formed by silver plating. Therefore, there were no voids in the heat generating layer. After 80,000 sheets had been fed, deformation occurred at a position corresponding to the edge of B5 size paper, resulting in poor image quality on A4 size paper. This is thought to be because the damping effect of the voids was not exerted. [Industrial Applicability]

[0130] As described above, according to at least one aspect of the present disclosure, a fixing rotating body that is highly durable even in a printing environment where high temperatures persist for long periods of time is provided. According to at least one aspect of the present disclosure, there is also provided a fixing device including the fixing rotor. According to at least one aspect of the present disclosure, there is also provided an electrophotographic image forming apparatus including the fixing device.

[0131] The present disclosure includes the following configurations. (Configuration 1) A fixing rotor, the fixing rotor comprising: A resin substrate; a heat generating layer extending on the outer peripheral surface of the resin substrate; a silicon dioxide layer on the outer peripheral surface of the heat generating layer and on the outer peripheral surface of the resin substrate in an area where the heat generating layer is not present; a resin layer on the outer peripheral surface of the silicon dioxide layer, the heat generating layer contains silver, the heat generating layer has holes at least partially filled with silicon dioxide and having openings on the resin layer side; The heat generating layer has pores. A fixing rotating body characterized by the above. (Configuration 2) 2. The fixing rotating member according to claim 1, wherein the silver is in the form of silver crystals, and the number average crystal grain size of the silver crystals is 500 nm or less. (Configuration 3) The fixing rotor according to configuration 1 or 2, wherein the proportion of pores in the cross section of the heat generating layer, as measured by observing a cross section of the heat generating layer sampled from the fixing rotor and cut in the thickness direction, is 15 to 50 area %. (Configuration 4) 4. The fixing rotatable member according to any one of configurations 1 to 3, wherein the heat generating layer has a thickness of 5.0 μm or less. (Configuration 5) 5. The fixing rotating member according to any one of configurations 1 to 4, wherein the silicon dioxide layer has a thickness of 1.00 μm or less. (Configuration 6) The fixing rotating body according to any one of configurations 1 to 5, wherein the compressive elastic modulus of the heat generating layer in a region of 10 to 20% in the thickness direction, measured by contacting an indenter with the surface of the heat generating layer opposite the surface facing the silicon dioxide layer, is 8 to 30 GPa. (Configuration 7) the heat generating layer has a plurality of segments arranged in the direction of the rotation axis of the fixing rotor and electrically isolated from one another; 7. The fixing rotor according to any one of configurations 1 to 6, wherein each of the plurality of segments is electrically continuous over the entire circumferential area of ​​the fixing rotor. (Configuration 8) The fixing rotating body according to any one of configurations 1 to 7, and an induction heating device that generates heat from the fixing rotor by induction heating. (Configuration 9) An electrophotographic image forming apparatus, The electrophotographic image forming apparatus comprises: an image carrier that carries a toner image; a transfer device that transfers the toner image onto a recording material; a fixing device that fixes the transferred toner image onto the recording material, 9. An electrophotographic image forming apparatus, wherein the fixing device is the fixing device according to Configuration 8. [Explanation of symbols]

[0132] 1 image forming apparatus, 15 fixing device, 20 fixing rotor, 20a resin substrate, 20b heat generating layer, 20c protective layer, 20d surface layer, 20e elastic layer, 20f adhesive layer, 21 pressure roller

Claims

1. A fixing rotor, the fixing rotor comprising: A resin substrate; a heat generating layer extending on the outer peripheral surface of the resin substrate; a silicon dioxide layer on the outer peripheral surface of the heat generating layer and on the outer peripheral surface of the resin substrate in an area where the heat generating layer is not present; a resin layer on the outer peripheral surface of the silicon dioxide layer, the heat generating layer contains silver, the heat generating layer has holes at least partially filled with silicon dioxide and having openings on the resin layer side; The heat generating layer has pores. A fixing rotating body characterized by the above.

2. 2. The fixing rotating member according to claim 1, wherein the silver is in the form of silver crystals, and the number average crystal grain size of the silver crystals is 500 nm or less.

3. The fixing rotor according to claim 1, wherein the proportion of pores in the cross section of the heat generating layer, measured by observing a cross section of the heat generating layer sampled from the fixing rotor and cut in the thickness direction, is 15 to 50 area %.

4. 2. The fixing rotor according to claim 1, wherein the heat generating layer has a thickness of 5.0 [mu]m or less.

5. 2. The fixing rotor according to claim 1, wherein the silicon dioxide layer has a thickness of 1.00 [mu]m or less.

6. 2. The fixing rotating member according to claim 1, wherein the compressive elastic modulus of the heat generating layer in a region of 10 to 20% in the thickness direction, measured by contacting an indenter with the surface of the heat generating layer opposite to the surface facing the silicon dioxide layer, is 8 to 30 GPa.

7. the heat generating layer has a plurality of segments arranged in the direction of the rotation axis of the fixing rotor and electrically isolated from one another; 2. The fixing rotor according to claim 1, wherein each of the plurality of segments is electrically continuous over the entire circumferential area of ​​the fixing rotor.

8. The fixing rotating body according to any one of claims 1 to 7, and an induction heating device that generates heat from the fixing rotor by induction heating.

9. An electrophotographic image forming apparatus, The electrophotographic image forming apparatus comprises: an image carrier that carries a toner image; a transfer device that transfers the toner image onto a recording material; a fixing device that fixes the transferred toner image onto the recording material, 9. An electrophotographic image forming apparatus, wherein the fixing device is the fixing device according to claim 8.

Citation Information

Patent Citations

  • Fixing member, fixing device, and image forming device

    JP2021051136A